Experimentation and use of cigarette and other tobacco products among adolescents in the Brazilian state capitals (PeNSE 2012) - Sandhi Maria Barreto; Luana Giatti; Maryane Oliveira-Campos; Marco Antonio Andreazzi; Deborah Carvalho Malta (Revista Brasileira de Epidemiologia, 2014)
INTRODUCTION: Nicotine dependence establishes itself more rapidly among adolescents than among adults. Tobacco occupies the fourth place in the rank of main risk factors for non-communicable diseases in the continent. Studies reveal that other forms of tobacco use have increased among adolescents. METHODS: Were included the 9th grade students from the 26 State Capitals and the Federal District. who were participants of the National Adolescent School-based Health Survey (PeNSE), in 2012. Factors independently associated with experimentation and regular use of cigarettes were investigated by means of multinomial logistic regression, using as reference "never tried a cigarette". The use of other tobacco products included cigar, pipe, narghile and others. RESULTS: Of the in the 61,037 participants in the 26 Brazilian capitals and the Federal District, 22.7% (95%CI 21.7 - 23.5) had experimented cigarettes, 6.1% (95%CI 5.6 - 6.6) are regular smokers and 7.1% (95%CI 6.5 - 7.7) had used other tobacco products, with half of them also being regular smokers. The chances of experimenting and being a regular smoker increased with age and according to the frequency of weekly exposure to other smokers. These chances were also higher among students who worked, who lived in monoparental families or without their parents, and those who felt that their parents would not mind if they smoked. CONCLUSION: Results reinforce the association between social disadvantages and experimenting and regular smoking. In addition, the use of other tobacco products is worthy of attention and may lead to regular smoking.